Corticosteroids in Pediatric Bacterial Meningitis: A Meta-Analysis of Randomized Controlled Trials Comparing Dexamethasone and Adjunctive Therapies - Ayudimartini, Ni Luh (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Bacterial meningitis remains a significant cause of morbidity and mortality in children. Adjunctive corticosteroid therapy, particularly dexamethasone, has shown promise in reducing inflammation and improving outcomes. This meta-analysis aimed to evaluate the efficacy and safety of dexamethasone compared to placebo or other adjunctive therapies in pediatric bacterial meningitis. Methods: A systematic search of PubMed, Embase, and the Cochrane Central Register of Controlled Trials was conducted from January 2013 to October 2024. Randomized controlled trials (RCTs) comparing dexamethasone with placebo or other adjunctive therapies in children with bacterial meningitis were included. Primary outcomes were hearing loss, neurological sequelae, and mortality. Secondary outcomes included adverse events. Data were pooled using a random-effects model, and the risk ratio (RR) with 95% confidence intervals (CI) was calculated. Results: Six RCTs met the inclusion criteria, comprising 2,840 children. Dexamethasone was associated with a significant reduction in hearing loss (RR 0.57, 95% CI 0.45-0.71, p=0.005) and neurological sequelae (RR 0.66, 95% CI 0.56-0.78, p=0.006) compared to placebo. No significant difference in mortality was observed (RR 0.78, 95% CI 0.49-1.27, p=0.32). The incidence of adverse events, including gastrointestinal bleeding and hyperglycemia, was similar between the dexamethasone and placebo groups. Conclusion: Adjunctive dexamethasone therapy in pediatric bacterial meningitis significantly reduces hearing loss and neurological sequelae without increasing mortality or the risk of serious adverse events.